(3QSGdI PGJ GdTYHJjf, hGdYed HgGs - (3GdMehj, ESeGYjd Hf gHI Gddgs
(3ChdgG (B:s
(3GdMeO ddg gPg QSGdI aj GdYed HPGJ GdTYHJjf hgj BdI TQjaI GSJNQLgG GdeJbOehf deYQaI CHYGO GdCLQGe aj GdWhd hGdYQV hGdHYO Hjf GdchcHjf hGdYQV hGdGQJaGYGJ hZjQgGs
(3BNQgG (B:s
(3GdHGH GdSGHY aUd aEPG YQafG GdHYO VQHfG GdHUQ GdChd hgh eGFI aj SJI hgj CMRGA ChdG hbSefG GdeHdZ Ydi GdSJjf jNQL ef GdbSeI YTQI hEf TFfG VQHfG GdHYO GdKGfj Jes
(3Vef eLehY NRGFfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B1\856s
(3cTa GdXfhf (B1\856s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3Gdadc hGdJfLje hGdejbGJs